PENYULUHAN MANFAAT IMUNISASI DASAR KEPADA MASYARAKAT DESA AJIJULU, KABUPATEN KARO - Anto, Endy Juli; Hutasoit, Eka Samuel P.; Rimbun, Surjadi; Sinaga, Inda M.; Manullang, Frengky S.; Situmorang, Novrina; Tiji, Widjaya Taufik; Situmeang, Ivonne Ruth Vitamaya Oishi; Tambunan, Ronald T. H.; Simanjuntak, Evirosa J.; Anjany, Larasaty; Kembaren, Alfri Yoganta S. (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
Community Service carried out by the Faculty of Medicine at the Universitas Methodist Indonesia by providing counseling about the benefits of basic immunization. Community Service was held 14-16 April 2023 in Ajijulu Timur Village, Tigapanah District, Karo Regency, North Sumatra. The counseling method used is by giving lectures, discussions and providing motivation. Question and answer discussions were carried out with the aim of gaining understanding, understanding and solutions as a form of solving problems and constraints faced by the local community. The results of this community service counseling and outreach are very effective considering that there are still many people who do not receive information about the benefits of immunization. With this counseling, the community becomes more aware of the importance of basic immunization. It is hoped that the people of Ajijulu will become more responsive and know how important this basic immunization is for infants, children and adolescents.